The use of SEM to investigate the effect of an electron beam on the optically-visible flashover treeing of MgO ceramic - Sutjipto, Agus Geter Edy; Takata, Masasuke (Springer Science+Business Media, 2007)
This paper introduces the use of a scanning electron microscope (SEM) to evaluate the insulation property of insulators under electron bombardment. An SEM may be used not only to observe a surface image but also to provide a fine electron beam for charging an insulator surface simultaneously. The distribution of electric field created by the surface charging can be developed by a simple model. The increase of electric field at the surface may exceed a critical value to experience a surface breakdown/optically-visible flashover. The insulation property is evaluated by measuring the period of charging/ electron bombardment, which is needed to initiate a treeing- formation (hereinafter time to flashover treeing/TTF). In this paper, under a 25 keV primary electron beam energy and for a magnification of 5000·, a 99.95% purity polycrystalline MgO specimen resulted in 7 min TTF. It was also observed that increasing the primary beam energy and the SEM’s magnification decreased the TTF. Therefore, at for a given energy and magnification, this method can be used to evaluate the insulation property of insulators under an electron beam environment.